Educational Potential of Multicultural Language Teaching (on the Russian Language Teaching Experience) - Gennadievna Shtyrlina, Ekaterina; Sergeevna Palekha, Ekaterina; Vladimirovna Kapralova, Julia (International Journal of Criminology and Sociology, 2022)
The educational potential of the language teaching environment does not often become the object of a special scientific description due to several objective reasons. The model of subject-subject educational relations between the Teacher and the Student in the conditions of the multicultural educational environment is analyzed in this article. This model is focused on supporting the relative autonomy of the individual in the process of teaching within the pedagogical process and is aimed at creating conditions that ensure the formation of humanistic value orientations based on the principle of cultural appropriateness. The article emphasizes the equivalence of the positions of participants in the educational space, the need to build a psychologically comfortable and humanistic interaction between them. The authors note that a new type of educational interaction should be of a dialogical nature and should be based on the principles of pedagogy of cooperation. Dialogue as the main form of interaction between subjects of the educational process implies a meeting of positions and points of view, in the process of which the views, ideas, opinions that could form the personality are determined, specified, enriched and transformed. The socio-cultural aspect of dialogue is important, where the dialogue participants are interpreted as the subjects of the dialogue of cultures. The discursive model of learning allows us to consider the text as a means of involving the individual in the cultural heritage and spiritual values of one’s own and other peoples (from text to culture and from culture to text). Using the pedagogical potential of the text, the teacher contributes to the formation of the learner’s necessary general educational competencies and his socio-cultural worldview. The article concludes that the educational text can be considered not only as a didactic unit but also as a unit for modeling cultural code, as a key tool for the formation of a person’s spiritual culture of the learner.